APRESENTAÇÃO DOS CADERNOS DO IL 55 - Hoff, Patrícia Cristine; Pavani, Cinara Ferreira; Silva, Silvana; Heineck, Débora; Monteiro, Evandro Oliveira; Habel, Jussara Maria; Ferreira, Melissa Osterlund; Passini, Michele Teixeira; Simionato, Deborah Mondari; de Freitas, Olivia Barros; da Costa, Monica Chagas (Cadernos do IL, 2017)
Apresentação do nº 55 dos Cadernos do IL - Número Especial/Estudos Linguísticos e Estudos Literários